(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The establishment of the first Sub-divisional Library atAizawl in the year 1969, Public libraries services are put under the supervision and control of the Department of Art Culture, Public Library Act 1993 which had been passed in Mizoram is not implement. In spite of efforts made by the library association the library services are not developing. Staff and financial allocation for public library services are inadequate. Most of the library staffs are non professional. The professional association in Mizoram is very active in promoting library services and aware the needs and importance of library to general public.